2‐Aminobenzamide‐Based Factor Xa Inhibitors with Novel Mono‐ and Bi‐Aryls as S4 Binding Elements. Issue 3 (18th January 2019) - Patel, Nirav R.; Patel, Dushyant V.; Kanhed, Ashish M.; Patel, Sagar P.; Patel, Kirti V.; Afosah, Daniel K.; Desai, Umesh R.; Karpoormath, Rajshekhar; Yadav, Mange Ram
Abstract: Factor Xa, a key serine protease in the coagulation cascade, has attracted a great deal of attention as a target for developing new antithrombotic agents. A series of novel alkyl, benzyl, biphenyl and substituted piperazine derivatives as S4 binding elements have been synthesized as potential human factor Xa (FXa) inhibitors with 2‐amino‐5‐chloropyridine as the S1 binding moiety. All the synthesized compounds were tested in vitro for FXa inhibitory activity by chromogenic substrate hydrolysis assay. The active compounds were selected to assess their ex vivo prothrombin time prolonging activity. Keeping in mind the promising in vitro and ex vivo profile of N ‐(5‐chloropyridin‐2‐yl)‐2‐(4‐(2‐cyanophenyl)benzylamino)benzamide (16 f ), it was selected for further in vivo evaluation of its antithrombotic potential. Structure‐activity relationship and molecular interaction analysis by the docking and dynamics studies within the series are discussed. Abstract : In an attempt to identify new antithrombotic agents, a series of novel 2‐aminobenzamide derivatives with alkyl, benzyl, biphenyl and substituted piperazine moieties as S4 binding elements were synthesized and tested for their in vitro FXa inhibitory activity. Based on its promising in vitro and ex vivo profile, compound16 f ( N ‐(5‐chloropyridin‐2‐yl)‐2‐(4‐(2‐cyanophenyl)benzylamino)benzamide) was selected to determine antithrombotic activity using In vivo FeCl3 induced arterial thrombosis model.